2016
DOI: 10.1159/000447666
|View full text |Cite
|
Sign up to set email alerts
|

Prediction of Poor Response to Modified Neuroleptanalgesia with Midazolam for Endoscopic Submucosal Dissection for Esophageal Squamous Cell Carcinoma

Abstract: Background/Aims: Modified neuroleptanalgesia (m-NLA) with midazolam is often used for sedation and analgesia during endoscopic submucosal dissection (ESD) for gastrointestinal neoplasia. However, interruption due to poor response to midazolam is often experienced during ESD for esophageal squamous cell carcinoma (ESCC) because most patients with ESCC have a history of heavy alcohol intake. We examined the incidence and risk factors for poor response to m-NLA with midazolam and pethidine hydrochloride. Methods:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 24 publications
(31 reference statements)
0
11
0
Order By: Relevance
“…Complete description of the ESD procedure has been reported . A bipolar needle knife (B knife; Xemex Co., Tokyo, Japan) and a monopolar needle knife (Flush knife, DK2618JN; Fujifilm Medical, Tokyo, Japan) were the main electrosurgical knives used.…”
Section: Methodsmentioning
confidence: 99%
“…Complete description of the ESD procedure has been reported . A bipolar needle knife (B knife; Xemex Co., Tokyo, Japan) and a monopolar needle knife (Flush knife, DK2618JN; Fujifilm Medical, Tokyo, Japan) were the main electrosurgical knives used.…”
Section: Methodsmentioning
confidence: 99%
“…Intravenous midazolam or propofol with pethidine hydrochloride was used to place patients under deep sedation during endoscopic procedures. 16 A single-channel upper gastrointestinal endoscope (GIF-Q260J; Olympus, Tokyo, Japan) and a standard electrosurgical generator (ICC 200 or VIO300D; ERBE Elektromedizin GmbH, Tübingen, Germany) were used. The main electrosurgical knives utilized were a bipolar needle knife (B knife; XEMEX, Tokyo, Japan) in the earlier study period and a monopolar needle knife (Flush knife, DK2618JN; Fujifilm Medical, Tokyo, Japan) in the later period.…”
Section: Methodsmentioning
confidence: 99%
“…This suggests that the stimulation by ESD affects the mechanical receptors in the muscular layer and extends beyond the muscular layer because of a lack of esophageal serosa. Esophageal pain may not be completely controlled by intravenous analgesics alone considering that body movements occur even when using intravenous analgesics, such as pethidine and pentazocine, under sedation during esophageal ESD . Although there have been no studies evaluating pain during esophageal ESD, esophageal post‐ESD pain was reported in 38.5–58.9% of cases .…”
Section: Discussionmentioning
confidence: 99%
“…Endoscopic therapy for early esophageal cancer is becoming widely used as a minimally invasive treatment. In particular, endoscopic submucosal dissection (ESD) results in a high en bloc resection rate and accurate pathological diagnosis even for large esophageal cancer . However, a high degree of technical skill is required to perform esophageal ESD because the esophagus has a narrow lumen and a thin wall.…”
Section: Introductionmentioning
confidence: 99%